Citrulline Accumulation Mechanism of Pediococcus acidilactici and Weissella confusa in Soy Sauce and the Effects of Phenolic Compound on Citrulline Accumulation - Zhou, Kai; Zhang, Xiao; Li, Bingyong; Shen, Chaoqun; Sun, Yuan-Ming; Yang, Jianyuan; Xu, Zhen-Lin (Frontiers in Microbiology, 2021)
Citrulline is one of the major precursors of ethyl carbamate in soy sauce, and the accumulation of citrulline is attributed to the metabolism of arginine by bacteria with the arginine-deiminase (ADI) pathway. However, the key strains and the factors affecting the citrulline accumulation are not yet clear. In this study, two key strains of Pediococcus acidilactici and Weissella confusa were isolated from soy sauce moromi, and the regularity of citrulline formation was studied. Results showed that the conversion rates from arginine to citrulline (A/C rate) and citrulline accumulation ability of W. Confusa and P. acidilactici significantly increased in the presence of different concentrations of NaCl, indicating that salt stress was the main factor for citrulline accumulation. The inconsistent expression of arc genes by salt stress was the reason for citrulline accumulation for P. acidilactici, but for W. Confusa, it may be due to the influence on transportation system of arginine/citrulline: the intracellular citrulline could not transport to extracellular space, nor converted into ornithine. Environmental factors greatly influenced citrulline accumulation of the two key bacteria, A/C rate and citrulline formation in both strains decreased at low temperature (15°C) under high salt stress, but opposite effects were observed for the two key strains under anaerobic light condition. Moreover, quercetin and gallic acid significant decreased A/C rate and citrulline accumulation ability of the two key strains. The optimal quercetin and gallic acid as suggested by simulation experiment were 100 mg/L and 10 mg/L, respectively, and the lowest A/C rate of 28.4% and citrulline level of 1326.7 mg/L were achieved in the simulation system. This study explored the main factors for citrulline formation by the two key strains and proposed a targeted way to control citrulline in soy sauce.